COMPULSORY MOTOR INSURANCE IN UZBEKISTAN AS A TOOL OF HOUSEHOLD FINANCIAL RESILIENCE AND REGULATED COMPENSATION - Abdujabborov , Islomiddin (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This thesis examines compulsory motor third-party liability insurance in Uzbekistan as a mechanism of household financial resilience, regulated compensation, and public trust in the insurance market. Unlike approaches that evaluate this insurance line mainly through premium growth or market share, this study interprets compulsory motor insurance as an institutional bridge between road-traffic risk, household financial protection, and formal claims settlement. The relevance of the topic is increasing because household motorization has grown considerably: in 2025, Uzbekistan had 61 passenger cars per 100 households, compared with 49 in 2020 and 21 in 2010 [3]. In parallel, the official insurance market data show that in 2025 motor third-party liability insurance generated UZS 406.165 billion in premiums, UZS 245.224 billion in claims payments, 6,221,221 active contracts, and 6,141,455 newly concluded contracts [2, pp. 6–7]. These figures indicate that compulsory motor insurance is not only a legal obligation for vehicle owners, but also a mass financial instrument through which accident-related losses can be transferred from individuals to a regulated insurance system. The thesis concludes that the future development of compulsory motor insurance in Uzbekistan should be assessed not only by contract volume, but also by claims transparency, adequacy of coverage, digital administration, and public confidence in the compensation process.